PENGANGGURAN DAN SOLUSINYA: TINJAUAN KRITIS ASPEK PENDIDIKAN - Rosidah, Rosidah (Jurnal Inovasi Pendidikan, 2010)
Unemployment issue has been a social problem that never ends. It is triggered by several causes such as monetary crisis, unbalance between the supply and demand, and unprepared working force. Many efforts through education have been done to overcome unemployment issue, for example through Competence Based Curriculum, Link and Match, and apprenticeship. The government has also determined some policies, namely Professional Autonomous Young Manpower (TKPMF), Educated Autonomous Manpower (TKMT), Effective and Efficient Technology (TTG), and Labor Force Opportunity Widening (PSPK). In addition, the government has also given opportunity to the society to become workers in foreign countries (TKI). Despite the efforts mentioned above, unemployment issue is still a problem in Indonesia. Viewing various phenomena related to this problem, many unemployment will be revealed thorough this writing to find the solutions by conducting critical analysis from educational aspect review.